Working Memory Performance for Differentially Conditioned Stimuli - Ward, Richard T.; Lotfi, Salahadin; Stout, Daniel M.; Mattson, Sofia; Lee, Han-Joo; Larson, Christine L. (Frontiers in Psychology, 2022)
Previous work suggests that threat-related stimuli are stored to a greater degree in working memory compared to neutral stimuli. However, most of this research has focused on stimuli with physically salient threat attributes (e.g., angry faces), failing to account for how a “neutral” stimulus that has acquired threat-related associations through differential aversive conditioning influences working memory. The current study examined how differentially conditioned safe (i.e., CS-) and threat (i.e., CS+) stimuli are stored in working memory relative to a novel, non-associated (i.e., N) stimuli. Participants (n = 69) completed a differential fear conditioning task followed by a change detection task consisting of three conditions (CS+, CS-, N) across two loads (small, large). Results revealed individuals successfully learned to distinguishing CS+ from CS- conditions during the differential aversive conditioning task. Our working memory outcomes indicated successful load manipulation effects, but no statistically significant differences in accuracy, response time (RT), or Pashler’s K measures of working memory capacity between CS+, CS-, or N conditions. However, we observed significantly reduced RT difference scores for the CS+ compared to CS- condition, indicating greater RT differences between the CS+ and N condition versus the CS- and N condition. These findings suggest that differentially conditioned stimuli have little impact on behavioral outcomes of working memory compared to novel stimuli that had not been associated with previous safe of aversive outcomes, at least in healthy populations.